THE CORRELATION BETWEEN STUDENTS READING ATTITUDE AND THEIR READING COMPREHENSION ACHIEVEMENT - Agustiani, Indah Windra Dwie (English Community Journal, 2017)
This study was aimed at finding out (1)) whether or not there was a significant correlation between students reading attitude and their reading comprehension,. The data were collected by distributing questionnaire sheets and testing a reading comprehension test for 170 students. Pearson Product Moment Coefficients Correlation and Regression Analysis were used to find out whether or not there was a significant relationship between students reading attitude toward reading comprehension achievement of the fourth semester students of English education study program of FKIP Universitas Muhammadiyah Palembang as well as their contribution. The findings of the study showed that, students reading attitude only had a very small contribution to their reading comprehension achievement.